Exercise Physiology Impairments of Patients With Amyotrophic Lateral Sclerosis: Cardiopulmonary Exercise Testing Findings - He, Ji; Fu, Jiayu; Zhao, Wei; Ren, Chuan; Liu, Ping; Chen, Lu; Li, Dan; Zhou, Lequn; Tang, Lu; Liu, Xiangyi; Ye, Shan; Liu, Xiaolu; et al. (Frontiers in Physiology, 2022)
Background and Objective In amyotrophic lateral sclerosis (ALS), progressive weakness significantly limits the ability to exercise. However, measurements of the impaired exercise function and their practical value to assess disease progression in ALS are scarce. Cardiopulmonary exercise testing (CPET) is a non-invasive accurate method used to comprehensively quantify exercise physiology in a variety of diseases. This study aimed to evaluate the clinical value of CPET and to explore its association with disease severity and prognosis prediction in ALS. Methods A total of 319 participants were enrolled in this 3-year prospective study. After strict quality control, 109 patients with ALS and 150 age- and sex-matched healthy controls were included with comprehensive clinical assessment and follow-ups. The incremental ramp protocol for symptom-limited CPET was applied in both groups. The exercise physiology during peak effort exercise was systematically measured, including the overall aerobic capacity of exercise (VO2 peak) and the respective capacity of the exercise-involved organs [cardiac response (heart rate peak—HR peak), ventilatory efficiency (VE/VCO2 slope), breathing economy (VE/VO2 peak), and other relevant parameters]. Disease severity and progression were evaluated using recognized scales. Survival was monitored with regular follow-ups every 6 months. Results Decreased exercise capacity (VO2 peak < 16 ml/kg/min) occurred more frequently in patients with ALS than in controls (44.95% vs. 9.33%, p < 0.01). In patients with ALS, the average VO2 peak (16.16 ± 5.43 ml/kg/min) and HR peak [135 (112–153) bpm] were significantly lower (p < 0.01) than in controls [22.26 ± 7.09 ml/kg/min; 148 (135–164) bpm], but the VE/VCO2 slope was significantly higher [28.05 (25.03–32.16) vs. 26.72 (24.37–29.58); p = 0.03]. In patients with ALS, the VO2 peak and HR peak were significantly correlated with disease severity and progression scores (p < 0.05). Survival analyses revealed the VO2 peak and HR peak as protective indicators while the VE/VO2 peak as a detrimental indicator for the prognostic prediction in ALS (HR = 0.839, p = 0.001; HR = 0.967, p < 0.001; HR = 1.137, p = 0.028, respectively). Conclusion Our prospective study quantified the significantly decreased exercise capacity in ALS through non-invasive CPET. The impaired VO2 peak and HR peak closely correlated with disease severity and independently predicted a worse prognosis. Our findings identified the clinical value of CPET as an objective indicator of disease progression in ALS.